Determining Employee Performance And Work Satisfaction Dimentionals In Multifinance Company Using Structural Equation Model Approach - Syahrani (Publisher Cv. Inara, 2021)
This study aims to determine the level of employee satisfaction with a structural model approach that can clarify the relationship between the variables of satisfaction, leadership work environment and employee performance. This research was conducted in a multinational company engaged in the multifinance sector, located in Banjarmasin, South Kalimantan, Indonesia In this study, the sample was taken using purposive sampling with a total sample of 235 people from various existing departments. The analytical technique used is the Structural Equation Model (SEM). The results of the study found that (1) the SEM model has met the standards of the Goodness of Fit Index, (2) the employee satisfaction variable has a significant influence on employee performance because it provides a CR value > 1.96 and a probability value < 0.05, (3) The work environment variable has an effect on significant on employee performance and satisfaction because it provides a CR value > 1.96 and a probability value < 0.05, (4) the leadership variable has a very significant influence on employee performance and satisfaction because it provides a CR value > 1.96 and a probability value < 0.05.